Simply Paradigm of Da’wah Character In Facing Neurotechnology Era - Nanang Kuswara (Dakwah Institut PTIQ Jakarta, 2020)
Since year 569 M, da’wah character has been organized around the exchange paradigm. Da’wah character for postindependence period, was faced with the life of Islam history which had been confessed as a cultural power. The concepts apply to all forms of exchange, as Al-Qur’an is compatible to all centenaries and places. Whether it is communicated by speaking efforts (bi al-lisan), writing (bi al-qalam), or by doing (bi al-hal). Da’wah character paradigm evolved from a verbal-conventional oriented view, physical efforts, and to expand to the highest network level of information technology system called neurotechnology. This paper use a literatur studies from the references that relevances with this theme. Theoretically, this article is developing of a three-tiered discourses of the emerging field of da’wah characters are explored - its sub phenomenon (Muslim sensory models), its phenomenon (da’wah character networks), and its super phenomenon (sustainability and development). The result of this article that consequently the relational theories have come to the fore. But even as the field struggles to grasp its new fields of explanation, there is a paradigm shift happening at its boundaries. The shift significantly integrates the da’wah character worldview by the theoretical tools and methodologies in frame syummuliyah and ‘alamiyah and based on Al-Qur’an and hadist (rabbaniyah), absolutly.